Recurrent spontaneous pneumothorax in pregnancy - a case report and review of literature - Noman Lateef; Mustafa Dawood; Karn Sharma; Abubakar Tauseef; Muhammad Asadullah Munir; Erin Godbout (Greater Baltimore Medical Center, 2018)
Spontaneous pneumothorax in pregnancy is a rare and life-threatening condition. In this report, a case of spontaneous pneumothorax occurring at 34 weeks' gestation in a healthy 34-year-old primigravida is described. She had typical complaints of chest pain and dyspnoea and diagnosis was made by chest X-ray which showed an extensive pneumothorax in the right side. Pneumothorax recurred twice over approximately three weeks. A caesarean section secondary to small pelvic parameters was scheduled with the chest tube in situ and a healthy 2.5 kg female infant was delivered. We discuss spontaneous pneumothorax during pregnancy and review the literature.